The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/acp.3801
|View full text |Cite
|
Sign up to set email alerts
|

Testing the seductive details effect: Does the format or the amount of seductive details matter?

Abstract: Summary A body of research indicates that the inclusion of seductive details in instructional materials negatively impacts learning. However, there is scant research that examines the format and the amount of seductive details as potential moderating factors across multiple learning outcomes. In two studies, one focused on seductive pictures and one on seductive text, we examined whether the amount of seductive details influenced learning performance on several outcomes. Experiment 1 participants were 88 middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, what happens when text is integrated with a seductive image? Seductive images are hypothesised to have a negative impact on working memory capacity by imposing extraneous cognitive load, since these images do not include information relevant to the learning task (Park et al, 2011(Park et al, , 2015Rey, 2012;Wang et al, 2021). Thus, when paired with text, the process of integrating information from multiple channels might serve a particular challenge for the learner.…”
Section: How Seductive Pictures Impact Cognitive Load In Multimedia E...mentioning
confidence: 99%
“…However, what happens when text is integrated with a seductive image? Seductive images are hypothesised to have a negative impact on working memory capacity by imposing extraneous cognitive load, since these images do not include information relevant to the learning task (Park et al, 2011(Park et al, , 2015Rey, 2012;Wang et al, 2021). Thus, when paired with text, the process of integrating information from multiple channels might serve a particular challenge for the learner.…”
Section: How Seductive Pictures Impact Cognitive Load In Multimedia E...mentioning
confidence: 99%
“…The literature has extensively investigated the seductive details effect of various media, including images (Wang et al, 2021), texts (Wang & Adesope, 2016), narrations (Park et al, 2015a), and animations (Abercrombie et al, 2019; Mayer et al, 2001). Nonetheless, it remains unclear whether a human character in a video would elicit a seductive details effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To this end, some studies have demonstrated that decorative pictures, which are considered seductive details, can enhance student interest (e.g., Magner et al, 2014; Wang & Adesope, 2016). A few studies also found positive effects on the part of seductive details on learning outcomes under specific conditions (e.g., Fries et al, 2019; Ketzer‐Nöltge et al, 2018; Lehmann et al, 2019; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%